PEMBUATAN SAMPUL BUKU DI PENERBIT DELS MEDIA UNTUK KARYA-KARYA TULIS PARA GURU - Rumekso, Kunto Adi (LPPM Institut Teknologi dan Bisnis Kristen Bukit Pengarapan, 2025)
An innovation can arise from creativity that is based on an understanding of what is happening around us, so that this creative process not only benefits oneself but can also be beneficial to others. Educators in this context, namely teachers in East Java, have their own methods of educating or applying their knowledge in teaching others. They are not confined to the classroom environment but instead utilize expressive media such as written works in novels, poetry anthologies, or educational textbooks. Creativity would be wasted without the means to support it, so Dels Media Publishing in Lamongan City has become one of the solutions to support the creativity of these teachers in publishing their written works. At Dels Media Publishing, the author is trusted as a cover designer, assisting in the book cover creation process while also demonstrating the author's support for the written works of the teachers.